2019
DOI: 10.1177/0300060519847376
|View full text |Cite
|
Sign up to set email alerts
|

Unusual rapid resolution of postsclerectomy exudative retinal detachment with topical NSAIDs therapy in a case of nanophthalmos

Abstract: Nanophthalmos is a developmental ocular malformation that has been associated with high risks of uveal effusion syndrome and exudative retinal detachment (ERD). A variety of surgical procedures and systemic/topical steroids have been described as effective for treatment of ERD. However, the possibility of side effects should be considered. Here, we describe a patient with nanophthalmos who was treated for recurrent ERD during long-term follow-up, and we discuss non-surgical treatment options that are available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…This aspect is particularly important when the interactions between the scotomas and eye movements are considered, as discussed hereinafter. Spatial distortion reported around central disciform scotomas caused, as a result of chorioretinal scaring after wet AMD, has been thought to be related to physical deformation of the retina near the scar at the scarring process 77,78 . The scotoma carving process results in such distortions without postulating any retinal mechanical distortions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This aspect is particularly important when the interactions between the scotomas and eye movements are considered, as discussed hereinafter. Spatial distortion reported around central disciform scotomas caused, as a result of chorioretinal scaring after wet AMD, has been thought to be related to physical deformation of the retina near the scar at the scarring process 77,78 . The scotoma carving process results in such distortions without postulating any retinal mechanical distortions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…20 However, the results of studies on corticosteroid therapy for the treatment of UE are not promising. 7 , 21 , 22 Other medical therapies such as topical non-steroidal anti-inflammatory drugs, topical prostaglandin analogs, and systemic carbonic anhydrase inhibitors have been reported only in a few case reports. 22 , 23…”
Section: Discussionmentioning
confidence: 99%
“…Shields et al [15] reported the treatment of 104 eyes of patients with UES and found that 95% of patients could be managed with steroids, and only 5% needed scleral window surgery. Tong et al [16] and Kumar et al [25] also demonstrated that nonsteroidal antiinflammatory drugs (NSAIDs) can be effective for UES treatment. Park and Lee [17] reported a 64-yearold UES patient successfully treated with topical latanoprost and oral acetazolamide as well as topical bromfenac without surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the mechanism proposed, a number of surgical procedures, in particular full or partial thickness multisclerectomy, have been promoted [11][12][13][14]. However, some patients have been successfully treated with systemic/ topical steroids [15], NSAIDs [16], latanoprost, and oral acetazolamide topical bromfenac [17,18]. Anti-VEGF agents combined with surgical intervention have been reported as a treatment option [9,10].…”
Section: Introductionmentioning
confidence: 99%